2010
DOI: 10.1189/jlb.0710386
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Advance: The promotion of soluble DC-SIGN release by inflammatory signals and its enhancement of cytomegalovirus-mediatedcis-infection of myeloid dendritic cells

Abstract: DC-SIGN is a member of the C-type lectin family. Mainly expressed by myeloid DCs, it is involved in the capture and internalization of pathogens, including human CMV. Several transcripts have been identified, some of which code for putative soluble proteins. However, little is known about the regulation and the functional properties of such putative sDC-SIGN variants. To better understand how sDC-SIGN could be involved in CMV infection, we set out to characterize biochemical and functional properties of rDC-SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…Whether they can be used prophylactically or therapeutically requires further evaluation. Given that the soluble forms of CD4 and DC-SIGN occur normally in vivo and that the Gly4Ser repeat linker is poorly immunogenic (43,44), further improvement of CLDs may render them potentially useful as prophylactic or therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Whether they can be used prophylactically or therapeutically requires further evaluation. Given that the soluble forms of CD4 and DC-SIGN occur normally in vivo and that the Gly4Ser repeat linker is poorly immunogenic (43,44), further improvement of CLDs may render them potentially useful as prophylactic or therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…DC-SIGN is a C-type lectin family member that is necessary for virus uptake [132]. It was shown that this release mediated infection of myeloid DCs by CMV and increased overall CMV infectivity [131]. HHV-6, another betaherpesvirus, has already been discussed in terms of the viral association with the endosomal pathway and MVBs.…”
Section: Epstein-barr Virusmentioning
confidence: 99%
“…Severe fever with thrombocytopenia syndrome virus was found to package virions within CD63 + extracellular vesicles (exosomes), which allowed for efficient receptor-independent uptake by neighboring cells [141]. Of note, pheleboviruses also have DC-SIGN as a receptor [142] , which has been shown to be packaged into exosomes for uptake in uninfected cells by CMV [131]. Further investigation should be undertaken to observe if a similar mechanism for viral spread is employed by phleboviruses and bunyaviruses in general.…”
Section: Bunyavirusesmentioning
confidence: 99%
“…DC-SIGN is a C-type lectin family member that is necessary for virus uptake [132]. It was shown that this release mediated infection of myeloid DCs by CMV and increased overall CMV infectivity [131].…”
Section: Epstein-barr Virusmentioning
confidence: 99%
See 1 more Smart Citation